33 What are the best settings and methods for recruitment into a randomised trial in severe breathlessness?. (13th October 2019) - Higginson, Irene; Wilcock, Andrew; Johnson, Miriam; Bajwah, Sabrina; Lovell, Natasha; Yi, Deokhee; Hart, Simon; Crosby, Vincent; Poad, Heather; Currow, David; Best, Emma; Brown, Sarah
Abstract : Limited drug treatments exist to relieve severe breathlessness in advanced disease. Antidepressants warrant consideration due to potential effects. However, trials are challenging. We aim to test the feasibility of a larger randomised mirtazapine trial, focusing on best settings and methods for recruitment. The BETter TreatmEnts for Refractory Breathlessness (BETTER-B feasibility) trial was a randomised, double-blind, placebo-controlled mixed-methods feasibility trial in London, Nottingham, Hull/York in adults with advanced diseases and modified Medical Research Council breathlessness scale (mMRC) scores of 3/4. We screened 409 patients, randomising 64 participants (30 mirtazapine, 34 placebo), averaging 1.8 patients per centre pcm. Existing antidepressant use was the main reason for ineligibility. 63% needed help completing questionnaires. Missing data were low. Participants (47 men) had a mean age of 72 (range 51–90) years. Primary diagnoses: chronic obstructive pulmonary disease (COPD) (40, 67%), interstitial lung disease (ILD) (19, 32%), cancer (1), heart failure (4). Several had multimorbidity. A 6.4:1 (16%) screen to recruit conversion suggests recruiting people with stage 3/4 mMRC breathlessness is possible. We consider screen to recruit ratios for different settings and diagnoses. Cancer patients were difficult to recruit. Achieving recruitment requires dedicated research teams. Six participants per arm stopped treatment prematurely; 4 mirtazapine, 5 placebo experienced serious adverse events (SAE); 1 (placebo) suspected as medication related. One participant per arm died, both unrelated to intervention. Qualitative data suggests feasibility and acceptability. A randomised double-blind phase III trial of mirtazapine is feasible and acceptable in patients with COPD/ILD, with low toxicity, and is warranted.